(3GdegGQGJ GdJShjbjI hGdGYdGejI ddTQcGJ GdOhGFjI (B/s - (3djOSJhf, Lhfs ((3GdLjRI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2009)
(3jVe EYOGO hEdbGA GdYQhV GdJbOjejI GdQSejI, YedjI GdJhGUd hSHd GdJYde, EYOGO GdYQV GdJbOjej, ebOeI GdYQV GdJbOjej, EOGQI GdYQV GdJbOjej hhSGFd GdYQV GdeQFjI, YbO GdeDJeQGJ GdeQFjI Yf HYO , GdYQhV GdeSehYI hGdeQFjI, SHd GdJYGed eY GdhSGFd GdEYdGejI, SHd ehGLgI hSGFd GdEYdGe, GdJYGed eY GdUMGaI, GdJOQjH Ydi GdegGQGJ GdEYdGejIs
Keywords: (3GdCOhjI(B- (3JShjbs; (3GdCOhjI, UfGYI hJLGQIs; (3GdUfGYGJ GdcjejGhjIs